Tandem Prins Strategy for the Synthesis of Spiropyrrolidine and Spiropiperidine Derivatives1. Issue 14 (2nd April 2015) - Reddy, Basi V. Subba; Yarlagadda, Suresh; Reddy, C. Ravikumar; Reddy, M. Rajashekhar; Sridhar, Balasubramanyan; Satyanarayana, Dayaka; Jagadeesh, Bharatam
Abstract: Cascade cyclization of a 3‐[(3‐methylbut‐2‐enylamino)methyl]but‐3‐en‐1‐ol derivative with aldehydes in the presence of TMSOTf at 0 °C under mild conditions provides the corresponding spiropyrrolidine scaffolds in good yields. Similar cyclization of a 3‐[(4‐methylpent‐3‐enylamino)methyl]but‐3‐en‐1‐ol derivative with aldehydes affords the correponding spiropiperidine compounds. This is a new approach for the construction of biologically relevant spirocycles in a single‐step process. Abstract : Cascade reactions between a 3‐[(3‐methylbut‐2‐enylamino)methyl]but‐3‐en‐1‐ol derivative and aldehydes in the presence of TMSOTf at 0 °C afford the corresponding spiropyrrolidine derivatives in good yields. Similar cyclization of a 3‐[(4‐methylpent‐3‐enylamino)methyl]but‐3‐en‐1‐ol derivative and aldehydes provides the corresponding spiropiperidines.